Time in postmodern novels: A study of slaughterhouse-five, time’s arrow and the sense of an ending - Arefin, Md. Maqsudul (BRAC University, 2014)
This thesis report submitted in partial fulfillment of the requirements for the degree of Bachelors of Arts in English at the Department of English and Humanities of BRAC University, 2014.